Financial sector development and investment in selected ECOWAS countries: Empirical evidence using heterogeneous panel data method - Chimere Okechukwu Iheonu; Simplice Asongu; Kingsley O. Odo; Patrick K. Ojiem (African Governance and Development Institute (AGDI), 2020)
This study investigated the impact of financial sector development on domestic investment in selected Economic Community of West African States (ECOWAS) countries for the years 1985 to 2017. The study employed the Augmented Mean Group procedure which accounts for country specific heterogeneity and cross sectional dependence, and the Granger noncausality test robust to cross sectional dependence. The result reveals that (1) the impact of financial sector development on domestic investment depends on the measure of financial sector development utilised, (2) domestic credit to the private sector has a positive but insignificant impact on domestic investment in ECOWAS while banking intermediation efficiency (i.e. ability of the banks to transform deposits into credit) and broad money supply negatively and significant influence domestic investment, (3) cross country differences exist on the impact of financial sector development on domestic investment in the selected ECOWAS countries, and (4) domestic credit to the private sector Granger causes domestic investment in ECOWAS. The study recommends cautiousness in terms of the measure of financial development which is being utilised as a policy instrument to foster domestic investment as well as the importance of employing country-specific domestic investment policies in order to avoid blanket policy measures. Also, domestic credit to the private sector should be given priority when forecasting domestic investment into the future.
Keywords: C5; E2; E5; G0; 330; Financial Sector Development; Domestic Investment; Augmented Mean Group; Granger non-causality test; ECOWAS